Penghayatan konsep 1Malaysia dalam pengajaran dan pembelajaran: Pengalaman UNITEN - Abdul Rahman, Noor Azam; Ahmad Tarmizi, Mohd Ariff (2011)
The 1Malaysia spirit first gained the attention of all parties when it revealed many positive effects for the long term development of the nation.Hence, scientific research related to this aspirational concept of the government needs to be more actively intensified.The application of 1Malaysia values can be done in many ways.It depends on the target group that we set.This concept, in general, must be applied to people from all walks of life.Among the important target groups that need awareness are students in institutions of higher learning as they are the generation that will lead the country in the future.This group is also the generation that will shape the nation in the long term. This study examines several ways of sowing and appreciating the 1Malaysia values used on undergraduates at UNITEN.This effort is emphasised through assignments given in subjects taught in Bahasa Malaysia.Generally, all the major subjects in UNITEN use the English Language as the medium of instruction in teaching and learning.However, there are several core university subjects for which Bahasa Malaysia is the medium of instruction.This study will explain the impact of the use of Bahasa Malaysia on sowing the spirit of 1Malaysia through the preparation of given assignments. The study bases its research on questionnaires distributed to 300 students taking the subject of Malaysian Studies in semester 2 of the 2009/2010 session at UNITEN.The results of this study reveal many positive effects that encourage students to accept and practise the government’s aspirational concept of 1Malaysia.